Schinzel-Giedion Syndrome with Congenital Megacalycosis in a Turkish Patient: Report of SETBP1 Mutation and Literature Review of the Clinical Features - Ozgul Bulut; Zeynep Ince; Umut Altunoglu; Sukran Yildirim; Asuman Coban (Case Reports in Genetics)
Schinzel-Giedion syndrome (SGS) is a rare autosomal dominant disorder that results in facial dysmorphism, multiple congenital anomalies, and an increased risk of malignancy. Recently, using exome sequencing, de novo heterozygous mutations in the SETBP1 gene have been identified in patients with SGS. Most affected individuals do not survive after childhood because of the severity of this disorder. Here, we report SETBP1 mutation confirmed by molecular analysis in a case of SGS with congenital megacalycosis.